Prevalence Rates and Predictors for Smoking Cigarettes Among Adolescents Attending School in Bissau, Guinea-Bissau - Geir Gunnlaugsson; Aladje Baldé; Zeca Jandi; Hamadou Boiro; Jónína Einarsdóttir (Adolescents)
Substance use is a growing problem among young people in sub-Saharan Africa who increasingly adopt the habit of smoking cigarettes. The aim was to analyse prevalence rates and identify predictors for cigarette smoking among school-attending adolescents in Bissau, Guinea-Bissau. In June 2017, a survey questionnaire was implemented in 16 schools in a class-based, random sample of 2039 adolescents aged 14–19 (52% girls). The chi-square (p < 0.05) and odds ratios (OR) were calculated with 95% confidence intervals (CI). Potential explanatory variables for the dependent variables were introduced into a multinomial logistic regression model, and p-values were transformed to LogWorth values. The prevalence rate for lifetime smoking experience was 14.8%, 4.0% for occasional smoking (<30 days), and 2.4% for daily smoking. The most significant predictors for cigarette smoking included having friends who smoke, being a boy, attending a private school, smoking initiation at a young age, other substance use, and violent behaviour. It is imperative to initiate preventive actions against smoking and other use of tobacco in Guinea-Bissau. Considering the significant impact of the peer group, policymakers need to engage young people in developing primary prevention strategies to curb the use of tobacco and other substances.